Socio Demographic Profile and Risk Factors Of Women Presenting With Cervical Cancer in A Tertiary Care Center in Bangladesh - Shirin, Fahmida; Ferdous, Jannatul; Karim, Tanjila; Islam, Fahmida; Khanam, Zubaida (Journal of Chittagong Medical College Teachers' Association, 2017)
Background : Bangladesh, a densely populated country of South-East Asia shows some of the highest rates of cervical cancer worldwide , and about 70% of the population is living in rural villages with a per capita GDP of 1211 US$ (Year 2015) having no population based cancer registry. The aim of this study was to assess the socio demographic status and risk factors related to cervical cancer in a tertiary care center in Bangladesh. Material and methods : A crosssectional study was conducted using a self administered questionnaire between January 1,2016 and June 30, 2016 on 68 patients who were admitted in Chittagong Medical College Hospital for confirmation of diagnosis and treatment. Results : Women of increasing age 40-50 (41.18%), having many pregnancies >4 ( 38.23%) and no education 63 (92.65%)with history of active or passive smoking 56 (82.36%) were found to be at increased risk of cervical cancer. Conclusion : It is important to recognize the socio demographic and risk factors associated with cervical cancer while making public health policies and implementation of cervical cancer control programmes. JCMCTA 2017 ; 28 (1) : 63 - 66